Given:
![\begin{gathered} f(x)=2x^2-4x-6 \\ g(x)\text{ = 3x-4} \\ h(x)\text{ = }(2)/(x) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nx0y1dx3rtklak6xpftoogcfs6q6mfegg8.png)
1.1.1 The equation of the reflection of g(x) in the x-axis is of the form:
The rule for the reflection in the x-axis:
![(x,y)\rightarrow\text{ (x,-y)}](https://img.qammunity.org/2023/formulas/mathematics/college/omxtkuit5jaerigii3tanorvvtqz8palxe.png)
Applying the rule:
![\begin{gathered} g^(\prime)(x)\text{ = -g(x)} \\ =-(3x\text{ -4)} \\ =\text{ 4 -3x} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ytvosqrs1n73fe3el26yarv7ngz999z0b3.png)
Hence, g'(x) = 4-3x
1.1.2 The equation of the reflection of h(x) in the y-axis.
The rule for reflection in the y-axis:
![(x,y)\rightarrow\text{ (-x,y)}](https://img.qammunity.org/2023/formulas/mathematics/college/lfb5tqpodkwhzw93vq7d0kkltfcb94u4po.png)
Applying the rule:
![h^(\prime)(x)\text{ = }(2)/(-x)](https://img.qammunity.org/2023/formulas/mathematics/college/d7g8y5298a4ovk68myftwhfsp5jra90pqm.png)
Hence, h('x) = 2/-x
1.1.3 The values of k for which :
![k=2x^2-4x-6](https://img.qammunity.org/2023/formulas/mathematics/college/qhlyhfodnuajc9g0n8dj85f2234niinsob.png)
Re-arranging:
![\begin{gathered} 2x^2-4x-6-k\text{ =0} \\ 2x^2-4x\text{ -(6+k) = 0} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ojmrod0f4t2dzn3gyg6blhbtictryj5wkh.png)
Using the rule that for an equation to have non-real roots, the discriminant (D) must be less than zero.
![\begin{gathered} D=b^2-4ac \\ (-4)^2\text{ -4(2)-(6+k) }<\text{ 0} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/21l3zem3uzy3rpvaxjd1cph6nuzfuvwq28.png)
Simplifying we have:
![\begin{gathered} 16\text{ +48+8k }<\text{ 0} \\ 64\text{ + 8k }<\text{ 0} \\ 8k\text{ }<\text{ -64} \\ \text{Divide both sides by 8} \\ (8k)/(8)\text{ }<(-64)/(8) \\ k\text{ }<\text{ -8} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s89s1rnzq2olmgu7v7iftpovjfgdkmekop.png)
Hence, the values of k for which the equation has non-real roots is that k must be less than -8
1.1.4 The average gradient of f(x) between x=-4 and x=0:
First, we need to find the value of f(x) at x=-4.
![\begin{gathered} f(-4)=2(-4)^2\text{ -4(-4) -6} \\ =\text{ 32+16 -6} \\ =\text{ 42} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/re79e57no8zntqanjlziomz8jwosngoju7.png)
Next, we must find the value of f(x) at x=0:
![\begin{gathered} f(0)=2(0)^2-4(0)\text{ -6} \\ =\text{ -6} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pl7rnkg4zwf1r9ksbvll8zgio5yi8pzv4v.png)
Using the average gradient formula:
![\begin{gathered} \text{Average gradient = }(y_B-y_A)/(x_B-x_A) \\ =\text{ }(-6-42)/(0-(-4)) \\ =(-48)/(4) \\ =\text{ -12} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/91z2n8xlvyip6ktxgzjiln9z3jqe90iu1o.png)
Hence, the average gradient is -12